Basel III and CEO compensation: a new regulation attempt after the crisis - Christian Eufinger; Andrej Gill (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The paper analyzes the interaction between an endogenous capital structure and investment decision, and the incentive scheme of bank executives. We show that the implementation of capital requirements, which are contingent on compensation schemes, drive a wedge between the interests of the shareholder and the CEO. This non-alignment can mitigate excessive risk taking. In particular, linking the amount of insured debt to the ratio of fixed and performance based salary encourages first-best outcomes. We derive empirical predictions and policy implications.
Keywords: G28; G32; G21; 330